Structural pattern extraction from asynchronous two-photon laser fault injection using spectral analysis. (September 2017) - Pouget, V.; Jonathas, S.; Job, R.; Vaillé, J.R.; Wrobel, F.; Saigné, F.
Abstract: This paper presents a methodology for analysing two-photon absorption laser testing results in the frequency domain rather than with the classical mapping approach. We experimentally demonstrate, on a 28 nm device, the extraction of subwavelength dimensions from a noisy environment without requiring any synchronization between the test operations and the laser or the scan motion. A model of the experiment is then used to evaluate the impact of different parameters on the capabilities of the technique. Highlights: Laser-injected faults are logged and analysed in the frequency domain. A sub-wavelength spatial period of a sensitivity pattern of the 28 nm SoC under test is extracted. The method requires no synchronization between the test-loop and the laser bench. The laser spot size is found to have no significant impact on the technique resolution.